Elucidation of target muscle and detailed development of dorsal motor neurons in chick embryo spinal cord. Issue 13 (17th July 2013) - Kobayashi, Nobumi; Homma, Shunsaku; Okada, Tomoaki; Masuda, Tomoyuki; Sato, Noboru; Nishiyama, Keiji; Sakuma, Chie; Shimada, Takako; Yaginuma, Hiroyuki
ABSTRACT The avian cervical spinal cord includes motoneurons (MNs) that send their axons through the dorsal roots. They have been called dorsal motoneurons (dMNs) and assumed to correspond to MNs of the accessory nerve that innervate the cucullaris muscle (SAN‐MNs). However, their target muscles have not been elucidated to date. The present study sought to determine the targets and the specific combination of transcription factors expressed by dMNs and SAN‐MNs and to describe the detailed development of dMNs. Experiments with tracing techniques confirmed that axons of dMNs innervated the cucullaris muscle. Retrogradely labeled dMNs were distributed in the ventral horn of C3 and more caudal segments. In most cases, some dMNs were also observed in the C2 segment. It was also demonstrated that SAN‐MNs existed in the ventral horn of the C1–2 segments and the adjacent caudal hindbrain. Both SAN‐MNs and dMNs expressed Isl1 but did not express Isl2, MNR2, or Lhx3. Rather, these MNs expressed Phox2b, a marker for branchial motoneurons (brMNs), although the intensity of expression was weaker. Dorsal MNs and SAN‐MNs were derived from the Nkx2.2‐positive precursor domain and migrated dorsally. Dorsal MNs remain in the ventral domain of the neural tube, unlike brMNs in the brainstem. These results indicate that dMNs and SAN‐MNs belong to a common MN population innervating the cucullaris muscle and also suggest that they are similar to brMNs of the brainstem, although there are differences in Phox2b expression and in the final location of each population. J. Comp. Neurol. 521: 2987–3002, 2013. © 2013 Wiley Periodicals, Inc.